(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the palliative care needs of hospitalized patients with head and neck cancer at Nghe An Oncology Hospital in 2026. Methods: A cross-sectional descriptive study was conducted among hospitalized patients with head and neck cancer at the Department of Internal Medicine 1, Nghe An Oncology Hospital, from January to April 2026. Results: The prevalence of palliative care needs among patients was 68.1%; while 31.9% of patients reported no such needs. The highest level of need was observed in the physical domain (76.3%); followed by the social domain (75.6%); the lowest rate was recorded in the area requiring assistance with activities of daily living (62.5%). Conclusion: Hospitalized patients with head and neck cancer had substantial and diverse palliative care needs. Their needs encompassed physical, social, spiritual and financial. Routine assessment of palliative care needs before hospital discharge, strengthening health education, providing home-care counseling, and enhancing coordination with community healthcare services are essential to improve the quality and continuity of care as well as patients’ quality of life.